SYMPOSIUM ON FOOT AND MOUTH DISEASE BRIEF REPORT ON THE DIAGNOSIS OF FOOT AND MOUTH DISEASE IN MEXICO - CAMARGO, FERNANDO (Instituto de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1947)
A technique is described by means of which a phenolic alkaloid of the isoquinaline group with an ether linkage was extracted from the leaves of the yoloxochitl Its empirical formula is C36H40O7Na According to its chemical structure this alkaloid should
LETT NUOVO CIM
Keywords: SYMPOSIUM, FOOT, MOUTH DISEASE, BRIEF REPORT, DIAGNOSIS, MEXICO; CIENCIAS DE LA VIDA; BIOLOGIA CELULAR; CULTIVO CELULAR